(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
Disc alumina membrane supports were formed through agar gelcasting method. The agar gelcasting was expected to be environmentally-friendly forming technique using simple equipment. Final agar amounts (0.25 – 0.75wt%) in gelcasting mixtures were varied to find the optimum condition of shaping and the desired microstructure of sintered supports. The gelcasting mixtures were prepared from non-reactive grade Al2O3 and porcelain at the ratio of 98.5:1.5 by weight. The porcelain addition allowed the membrane support to have high strength at lower sintering temperature. When the final agar amounts increased from 0.25 to 0.75wt%, the dried, gelcast supports tended to have rough surface and subsequently resulting in crack. TGA profiles confirmed that there was interaction between agar chains and kaolin particles on cooling the gelcast supports leading to different microstructures after sintering. The final agar amount of 0.5 wt% provided the highest porosity of 48.9% and the highest relative density of 61.5%. Additionally, the average pore size of 1.5 µm was obtained at the final agar amount of 0.5 wt% suitable for using as asymmetric membrane support or microfiltration membrane.